Presentation Pattern of Retinoblastoma - Israr Ahmed Bhutto, Umair Qidwai, Sadia Bukhari, Aziz-ur-Rehman (Pakistan Journal of Ophthalmology, 2011)
Purpose: To determine the pattern of presentation of retinoblastoma. Materials and Methods: This is a retrospective case series based on clinical records of patients less than 15 years identified with retinoblastoma from January 2006 to December 2009. Demographic characteristics including; presenting symptoms and signs, family history, age, gender, laterality and provided treatment were analyzed. Results: Sixty two patients with retinoblastoma were identified, out of which 79% had unilateral involvement while 21% had bilateral involvement. The most common sign of presentation was leukocoria 56.5% followed by proptosis 24.2%. Other presenting signs include fungating mass in orbit, red and watery eyes with raised intraocular pressure and diffuse vitreous haze. Conclusion: The most common presenting sign is leukocoria but proptosis also accounts for significant number of cases. Because of delay in presentation and diagnosis of retinoblastoma preservation rate of globe is very low. Raising awareness and education of primary health care providers and parents is strongly recommended.